Acute and sub-chronic Toxicity of Tri-Sa-Maw recipe in rats - Urarat Nanna (2018)
© 2015, Medical Association of Thailand. All rights reserved. Background: Tri-sa-maw recipe is a botanical preparation comprised of equal proportions of the three herbal fruits, namely Terminalia chebula Retz., Terminalia sp. and Terminalia bellirica Roxb. This recipe is used for antipyretic, expectorant, periodic maintenance, and relieving stomach tight. Objective: To evaluate the acute and sub-chronic toxicities of Tri-sa-maw recipe extract in rats. Material and Method: In the present study of acute toxicity, a single oral dose 5,000 mg/kg of Tri-sa-maw recipe extract was administered to rats. Sub-chronic toxicity was studied by the daily oral administration of the extract at the doses of 600, 1,200 and 2,400 mg/kg body weight for consecutive 90 days. Results: Tri-sa-maw recipe extract at the dose of 5,000 mg/kg showed no signs of differences as compared to the control rat. No abnormalities were found in the sub-chronic toxicity study; none of the parameters for body and organ weights, hematology, blood chemistry, necropsy, and histopathology showed any differences between the control and all treatment groups. Conclusion: Tri-sa-maw recipe extract did not significantly cause acute toxicity or sub-chronic toxicity in rats.